Strategi Dakwah Digital Mencegah Inhirf as-Sulk Remaja Muslim dari Gaming Menuju Judi Online - Maftukhatul Azizah; Altruis Bizurai Chillyness; Lilik Hamidah (Sekolah Ilmu Dakwah dan Komunikasi Islam (STIDKI) Ar Rahmah, 2025)
The development of digital culture in the modern era has triggered changes in the behavioral patterns of Muslim adolescents, including a shift from digital gaming entertainment activities to online gambling practices. This phenomenon represents inhir?f as-sul?k or behavioral deviations influenced by weak self-control, exposure to the digital environment, and limited religious literacy in the virtual space. This study aims to analyze digital da'wah strategies in preventing inhir?f as-sul?k in Muslim adolescents using the perspective of Everett M. Rogers' Diffusion of Innovation theory. This study uses a qualitative approach through a literature review of scientific journals and academic books on digital da'wah, adolescent behavior, and the adoption of communication innovations. The units of analysis include concepts, models, and empirical findings related to the process of adopting da'wah messages in digital media. Data are analyzed thematically and comparatively by linking the stages of innovation diffusion and digital da'wah practices. The results of the study indicate that the effectiveness of digital da'wah is determined by content innovation, the use of social media, and message adjustments according to the adoption stage. This research provides a conceptual contribution